APPROACH OF RECIPROCAL TEACHING AS THE SOLUTION FOR AN ENGLISH READERS - Imran Trista Udin (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
The objectives of this research were to find out whether or not reciprocal teaching technique improve the students’ reading skill of the tenth-grade students of class X 1 at SMA Negeri 4 Makassar. This research applied a pre-experimental with pre-test and post-test design. The population was the tenth-grade students of class X 1 at SMA Negeri 4 Makassar, in 2023/2024 academic year. The population consisted of 49 students where the sample was taken by using purposive sampling technique. The research data were collected by pre-test and post-test on speaking test and analyzed by using IBM SPSS 23 version to see the significant difference between pre-test and post-test. The results of the research were the application of reciprocal teaching technique significantly improved the students’ reading skill. The researcher concluded that reciprocal teaching can be the alternative choice for teaching English at SMA (Senior High school).